Structural response of metal foam cored sandwich structures - Tay, Yong Zhen. (2012)
Aluminium sandwich structures are gaining prominence in designing automotive, aerospace and military applications. In this project, the failure response of clamped sandwich circular plates has been investigated experimentally and numerically. The sandwich plates consist of aluminum alloy foam core of approximately 9% relative density and half-hard aluminum face sheet. Four failure modes were analyzed in this report namely indentation, core shear, face sheet yielding and face sheet punching. The results from the numerical simulation would be considered in modeling other sandwich structure application. Finite element method is more essential involving large model where experiment testing was not suitable. Finite element method could also save the designer’s time and budget.